Natural and anthropogenic influence on soil erosion in a rural watershed in the Brazilian southeastern region - Sobral, Anahi Chimini; Palcheco Peixoto, Anna Silvia [UNESP]; Nascimento, Victor Fernandez; Rodgers, John; Silva, Alexandre Marco da (Springer, 2015)
Human activities have been driven land cover, provoking acceleration of the erosive process and alteration on the soil characteristics. To explore the effects of human disturbance, we investigated the influences of natural and anthropogenic features on soil quality and soil erosion indicators (EI) within a Brazilian rural watershed located in Bauru Municipality, State of So Paulo. A pre-established set of soil EI was used to evaluate the influence of anthropogenic land cover categories on the presence and severity of erosion, related with spatial variations of soil attributes. On-site visits were carried out to measure the occurrence and the intensity of eleven separate EI values and to collect undisturbed topsoil samples for subsequent analyses. We registered 17 occurrences of EIs, distributed in ten locals. Occurrence and intensity of EIs were related to degree of sheet erosion. The EI qualities were more strongly associated with land cover management practices than to local topographic features. The occurrence of EIs and characteristics of soil and soil organic matter (SOM) were not significantly self-correlated. Although land cover class seems to influence soil properties and SOM attributes, we observed that the granulometric composition of the soils also contributes to the structural characteristics of the soil and consequently to the dynamic loss and gain of soil carbon. Sites covered with natural remnant vegetation (NRV) store 96.5 Mg ha(-1) of C and grassy and tilled soils stored more C than NRV, 100.1 and 142.4 Mg ha(-1), respectively. Due to the influence of soil texture over the soil C dynamic, we observe that in Bauru, pastured areas have high potential for sequestration of C if factors such as fire and/or erosion were avoided or effectively controlled. Results from this study show that human disturbance substantially affects soil properties within of southeastern region of Brazil.
Keywords: Land cover change; Human disturbance; Land use sustainability; Soil erosion indicators; Bauru-SP-Brazil